TWO-PHASE DYNAMICS OF BONE MARROW MULTIPOTENT MESENCHYMAL STROMAL CELLS (MMSC) ACTION ON LIVER AT MODELING OF FIBROTIC HEPATITIS - N. A. Onishchenko; A. V. Lyundup; I. M. Gazizov; R. V. Deev; M. Y. Shagidulin; М. Е. Krasheninnikov; P. V. Avramov (Вестник трансплантологии и искусственных органов, 2011)
Under the modeling of chronic fibrousing hepatitis in rats (n = 75) the dynamics of fibrolytic effect of bone mar- row MMSC was examined after one or two-time infusion of these cells at the early stage of liver fibrosis. By dynamic measuring of liver fibrotic area and the expression of activated stellate cell markers (desmin, α-SMA) and markers of cell apoptosis (caspase-3 and caspase-9) within 90 days two phases of the development of bone marrow MMSC fibrolytic effect were found. It is shown that the development of fibrolytic effect includes the primary phase of intensification of fibrosis, which is followed by the phase of enhanced fibrolytic process in the liver. It was determined that the two-phase dynamics of liver regeneration was more intensive after two-time infusion of bone marrow MMSC.